An overview of salinity stress, mechanism of salinity tolerance and strategies for its management in cotton - Maryum, Zahra; Luqman, Tahira; Nadeem, Sahar; Khan, Sana Muhy Ud Din; Wang, Baohua; Ditta, Allah; Khan, Muhammad Kashif Riaz (Frontiers in Plant Science, 2022)
Salinity stress is one of the primary threats to agricultural crops resulting in impaired crop growth and development. Although cotton is considered as reasonably salt tolerant, it is sensitive to salt stress at some critical stages like germination, flowering, boll formation, resulting in reduced biomass and fiber production. The mechanism of partial ion exclusion (exclusion of Na+ and/or Cl–) in cotton appears to be responsible for the pattern of uptake and accumulation of harmful ions (Na+ and Cl) in tissues of plants exposed to saline conditions. Maintaining high tissue K+/Na+ and Ca2+/Na+ ratios has been proposed as a key selection factor for salt tolerance in cotton. The key adaptation mechanism in cotton under salt stress is excessive sodium exclusion or compartmentation. Among the cultivated species of cotton, Egyptian cotton (Gossypium barbadense L.) exhibit better salt tolerance with good fiber quality traits as compared to most cultivated cotton, because of its origin near sea coasts and it can be used to improve five quality traits and transfer salt tolerance into Upland or American cotton (Gossypium hirsutum L.) by interspecific introgression. Cotton genetic studies on salt tolerance revealed that the majority of growth, yield, and fiber traits are genetically determined, and controlled by quantitative trait loci (QTLs). Molecular markers linked to genes or QTLs affecting key traits have been identified, and they could be utilized as an indirect selection criterion to enhance breeding efficiency through marker-assisted selection (MAS). Transfer of genes for compatible solute, which are an important aspect of ion compartmentation, into salt-sensitive species is, theoretically, a simple strategy to improve tolerance. The expression of particular stress-related genes is involved in plant adaptation to environmental stressors. As a result, enhancing tolerance to salt stress can be achieved by marker assisted selection added with modern gene editing tools can boost the breeding strategies that defend and uphold the structure and function of cellular components. The intent of this review was to recapitulate the advancements in salt screening methods, tolerant germplasm sources and their inheritance, biochemical, morpho-physiological, and molecular characteristics, transgenic approaches, and quantitative trait loci (QTL) for salt tolerance in cotton.